A Case report of coronavirus disease-19-associated pulmonary aspergillosis and pneumothorax (Indian Journal of Case Reports, 2021)
Secondary infections in coronavirus disease (COVID)-19 pneumonia in association with lung cavitation are rare findings. The development of cavitation has been attributed to aseptic liquefaction of pulmonary thromboemboli or secondary infection, resulting in the formation of pneumatoceles. Rupture of a large pneumatocele may lead to the development of pneumothorax. We report the case of a 56-year-old male who was treated for COVID-19 pneumonia with severe acute respiratory distress syndrome (ARDS) but developed pneumothorax and a cavitary lesion in the recovery period. This was further complicated by a co-infection with Aspergillus fumigatus in endotracheal secretions. The pneumothorax failed to resolve and there was a failure to wean off mechanical ventilation, culminating in death after 2 weeks. This case report highlights the need to monitor for small pneumatoceles even in the recovery phase of COVID-19 which may predispose to pneumothorax or pneumomediastinum.